Comparative and normative analysis of damages under the SGA and the CESL - Beheshti, Reza (St. Thomas University School of Law, 2014)
The Proposal for a Common European Sales Law (CESL) and the Sale of Goods Act 1979 (SGA) have adopted different approaches toward the calculation of damages. Under the SGA, the ‘market price’ rule is preferred over the rule governing ‘making a substitute transaction’. Where there is a market price for the contract goods, a higher or lower price at which the buyer has made a cover purchase for the similar goods is generally irrelevant to the assessment of damages. Conversely, under the CESL, the ‘market price’ rule for calculation of damages is subsidiary, even if the ‘market price’ rule would have been more advantageous for the buyer. This paper will compare these different mechanisms for calculating damages within the context of international sales of manufactured goods. This comparison is based on a novel normative framework. This normative framework consists of four criteria: 1) legal certainty, an essential requirement of international sales transactions; 2) performance interest, reflecting the specific needs of a buyer entering a commercial transaction; 3) efficiency, concerning whether the remedy can minimize transaction costs facing the disputants; and 4) satisfying the norms of relational theory, as international sales of manufactured goods requires a continuing relationship between the parties in different stages of contract. This comparison aims to identify which legal regime has adopted the more appropriate approach in accordance with the normative framework. Finally, proposals for improving the rules of monetary damages under the CESL, which seems to have some defects, are suggested.